Effects of coupling agent on mechanical properties and water absorption of oil palm frond-polypropylene composite / Nor Farhana Jasmi, Jamaludin Kasim and Muslyza Che Hussin - Jasmi, Nor Farhana; Kasim, Jamaludin; Che Hussin, Muslyza (2015)
Oil palm frond is reported to be the biggest amount of solid biomass from oil palm plantation. In supporting the zero burning system implied today, the cut fronds are left at the plantation as natural fertilizers. The main idea in this research is to utilize the leftover cut fronds as filler in polypropylene matrix composite rather than for bio-fertilizers. However, the hydrophilic natural particles tend to have difficulties to be encapsulated by the hydrophobic matrix. Thus, this paper investigated the effectiveness of coupling agent to improve the interfacial adhesion between oil palm frond and polypropylene matrix. Composites with two different particle sizes were fabricated with 0% and 3 wt% coupling agent through hot-press moulding. The findings of maleic anhydride polypropylene (MAPP) variable performed a significant difference at 95% confident level in all tested samples except for the flexural modulus and impact strength. In general, MAPP improved the composite properties of flexural, tensile, impact and water absorption behaviour.